2022
DOI: 10.1101/2022.08.17.504141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cancer tissue of origin constrains the growth and metabolism of metastases

Abstract: Metastases arise from a subset of cancer cells that disseminate from the primary tumor; however, the factors that contribute to proliferation of cancer cells in a secondary site are incompletely understood. The ability of cancer cells to thrive in a new tissue site is influenced by genetic and epigenetic changes that are important for disease initiation and progression, but these factors alone do not predict if and where cancers metastasize. Specific cancer types metastasize to consistent subsets of tissues, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
2
2
0
Order By: Relevance
“…The finding that FA metabolism is already altered in a p53-dependent manner in primary BCs is biologically important. It is in full agreement with a recent study that demonstrated that the metabolic programs of primary tumors were very similar to those of their metastases, arguing that cancer cells retain many aspects of a metabolic program that is defined by the tissue-of-origin even when exposed to a new metastatic niche ( 82 ). That study concluded that despite much evidence for specific metabolic adaptations within metastatic niches, the metabolic program of the primary tumors may constrain cancer metastasis ( 82 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding that FA metabolism is already altered in a p53-dependent manner in primary BCs is biologically important. It is in full agreement with a recent study that demonstrated that the metabolic programs of primary tumors were very similar to those of their metastases, arguing that cancer cells retain many aspects of a metabolic program that is defined by the tissue-of-origin even when exposed to a new metastatic niche ( 82 ). That study concluded that despite much evidence for specific metabolic adaptations within metastatic niches, the metabolic program of the primary tumors may constrain cancer metastasis ( 82 ).…”
Section: Discussionsupporting
confidence: 91%
“…It is in full agreement with a recent study that demonstrated that the metabolic programs of primary tumors were very similar to those of their metastases, arguing that cancer cells retain many aspects of a metabolic program that is defined by the tissue-of-origin even when exposed to a new metastatic niche ( 82 ). That study concluded that despite much evidence for specific metabolic adaptations within metastatic niches, the metabolic program of the primary tumors may constrain cancer metastasis ( 82 ). This is in line with older gene expression analyses showing that the metastatic potential of human tumors is encoded in the bulk of the primary tumor ( 83 ).…”
Section: Discussionsupporting
confidence: 91%
“…Mechanisms that determine a cancer cell's metastatic fate toward one organ site over another are poorly understood and are not sufficiently accounted for by a model of serial, divergent acquisition of somatic mutations 33,34 . The fact that cancer types with different oncogenic dependencies and distinct lineages exhibit a shared preponderance for metastasis to a specific organ (for example, LM in both melanoma and colorectal cancer) suggests that target-organ-specific adaptations occur and may be determined by the required metabolic requirements and phenotypic plasticity 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Filled graphs in (b,c) indicate viral concentration/dilution used for the large-scale CRISPR screen. d, Pearson correlation coefficient of the normalized sgRNA read counts from Brie plasmid pool, transduced cells in vitro edited over time (10,14,21,28,35,42,49,56 days after spin infection), from primary tumors (n = 8), from liver (n = 14), lung (n = 3), and lymph node (n = 8) metastases. For each biological sample type, biological replicates (R1, R2, R3… R8), for technical replicates (R3.1, R3.2) are shown.…”
Section: Articlementioning
confidence: 99%